Gold Nanoparticles: Innovative Supramolecular Platforms for Targeted Drug Delivery and Bioorthogonal Catalysis - Pawar, Anil; Zade, Alka; Shastri, Aarti; Ingole, Ramesh; Kharde, Sagar; Rajguru, Jeevan (Indian Journal of Pharmaceutical Education and Research, 2026)
Gold Nanoparticles (AuNPs) have gained significant attention across multiple fields, including drug delivery, therapy, sensing, material science and catalysis, due to their tunable properties. These nanoparticles exhibit high stability, water solubility, biocompatibility and chemical versatility, primarily attributed to the Self-Assembled Monolayers (SAMs) of organic ligands on their metal cores. Key features such as size, shape and surface functionality play a critical role in determining their interactions with biological systems, influencing uptake, distribution, cytotoxicity and biomolecular interactions. The aim of this review is to provide an in-depth analysis of the application of AuNPs in drug delivery and therapy, highlighting their role in drug conjugation, controlled release and targeted therapeutic interventions. Additionally, the review aims to explore the expanding domain of bioorthogonal catalysis and its relevance to drug delivery systems. This study focuses on reviewing various research articles and case studies that discuss the principles of supramolecular chemistry related to AuNPs. Specifically, it examines methods of drug conjugation, the process of self-assembly in supramolecular drug delivery systems and the application of transition metal catalysts in bioorthogonal catalysis. Key breakthroughs in the field, including advancements made by researchers like Meggers and Bradley, are analyzed to illustrate the cutting-edge developments in the use of AuNPs. The analysis reveals that AuNPs can significantly enhance drug delivery by enabling precise targeting and controlled release. Their interaction with complementary molecules allows for tailored therapeutic interventions. In bioorthogonal catalysis, AuNPs demonstrate the ability to perform targeted conversions and synthetic reactions, with key achievements in intracellular catalytic processes. The versatile properties of AuNPs, particularly their ability to participate in supramolecular self-assembly and bioorthogonal catalysis, position them as promising tools for advancing drug delivery and therapeutic applications. Their unique characteristics hold great potential to revolutionize targeted drug administration and bioorthogonal catalytic techniques in modern medicine.
Keywords: Bioorthogonal Catalysis; Drug Delivery; Gold Nanoparticles; Supramolecular; Chemistry